A method for preparing synthetic wollastonite refined slag
Through low-temperature sintering method and hydrothermal synthesis technology, combined with fiber reinforcement and heating of two-stage gas generators, the high energy consumption and low strength of wollastonite refined slag is solved, and the production of wollastonite refined slag is achieved with high efficiency, energy-saving and environmentally friendly wollastonite refined slag is achieved. Improves the purification effect of molten steel.
Patent Information
- Application Number
- CN202310095633.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-10
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2043-02-10
AI Technical Summary
In the prior art, the melting method produces wollastonite refined slag with high energy consumption, high pollution and high emissions. The sintering method produces small particles and low strength, resulting in environmental pollution and waste of raw materials.
Using low-temperature sintering method and hydrothermal synthesis technology, high-purity hydrated calcium silicate is generated through the hydrothermal reaction between wollastonite tailings and ripped lime, fiber reinforcement is added and pressure-formed, combined with two-stage gas generators to control sintering Temperature and time form high-strength wollastonite refining slag.
It reduces energy consumption, improves the particle diameter and strength of the product, reduces dust generation, realizes high-quality grading and utilization of resources, and improves the level of steel purification technology.
Smart Images

Figure CN116144881B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of novel inorganic materials, and particularly relates to a production process technology of metallurgical auxiliary materials, and specifically is a method for preparing synthetic wollastonite refined slag. Background Art
[0002] Synthetic wollastonite refining slag has stable composition, high purity, neutral alkalinity, good fluxing property, low oxygen potential, low melting point, easy modification and adsorption of inclusions, etc. It can effectively remove inclusions such as aluminum oxide in molten steel and is the preferred refining material for clean steel. When producing wollastonite refining slag by melting method, a large amount of heat energy is required, such as the patent "Artificial wollastonite and its preparation method" with publication number CN1199908C, which provides an artificial wollastonite containing oxides of elements such as calcium, silicon, aluminum, magnesium, sodium, boron, barium and calcium fluoride. The raw materials are crushed and mixed and then put into the kiln, fired at a high temperature of about 1600°C, and then cooled by natural cooling or water quenching. The production process is high-temperature melting and has high energy consumption; the water quenching and cooling process step wastes a lot of heat energy and water resources. At the same time, the product particles after water quenching are small (only about 1-2mm), and dust is easily formed during the addition process of molten steel purification process, causing environmental pollution and waste of raw materials.
[0003] The sintering method is used to synthesize wollastonite refined slag. Due to the low ball strength, it is easy to break during packaging, transportation, and use, which affects the technical effect. The patent "A sintered calcium magnesium silicate refined slag for cord steel and its preparation method" (publication number CN109439845A) with an application date of December 26, 2018 provides a sintered calcium magnesium silicate refined slag for cord steel. The preparation method requires grinding the raw materials into powder, mixing the powder raw materials evenly, and directly putting them into a rotary kiln. Calcination at 1350-1550℃ until agglomerates are transferred out of the kiln, and sintered calcium magnesium silicate refined slag is obtained. Because the refined slag is sintered only with powder, the powdered material is rolled into balls during the sintering process, resulting in low product strength and easy to break and pulverize. The pulverized refined slag cannot achieve the ideal effect of purifying molten steel when used, and also pollutes the environment. Summary of the invention
[0004] In order to overcome the defects of the above-mentioned prior art, the present invention aims at the problems of high energy consumption, high pollution and high emission in the production of molten wollastonite refining slag, and uses tailings to reduce product energy consumption by low-temperature sintering; at the same time, the product particle diameter and particle strength are improved to solve the problems of small pre-melted refined slag particles and high dust generation in the prior art; and low strength and easy pulverization of sintering products; and through the optimization of component indicators, the level of molten steel purification technology is improved.
[0005] To achieve the above-mentioned object of the invention, the present invention provides a method for preparing synthetic wollastonite refined slag, comprising the following steps:
[0006] ① Take wollastonite tailings with SiO2 mass content greater than 70% and CaO mass content greater than 18%, grind them into tailings powder with 800 mesh pass rate greater than 95%, add water to prepare the tailings powder into a slurry with a mass concentration of 40%.
[0007] Natural wollastonite is often associated with quartz, which makes wollastonite contain a large number of "silicon nodules"; in the beneficiation process, these "silicon nodules" will be screened out and become tailings; the outstanding feature of this tailing is the high content of SiO2 in its composition. In view of this characteristic of this type of tailings, its application field is developed to make it a resource. In the structure of wollastonite tailings, due to the presence of Ca-O bonds, the reaction activity of SiO2 is increased, which is conducive to the hydrothermal synthesis reaction with slaked lime; at the same time, the finer particle size can also promote the acquisition of high-purity and good-crystallinity hydrated calcium silicate products in a short time.
[0008] ② Take lime with a CaO content greater than 85%, add water at 40% of the CaO content to dissolve it into lime milk. The dissolution temperature is 95°C, the dissolution time is 30-40 minutes, and the stirring speed is 450-500rpm.
[0009] During the hydrothermal process, slaked lime dissolves to increase the alkalinity of the solution, which is beneficial to the dissociation of SiO2 and ensures the production of silicate anions; on the other hand, it provides silicate cations to balance the charge of silicate anions and form a silicate structure.
[0010] ③ The tailings powder slurry obtained in step ① and the lime milk obtained in step ② are mixed according to a SiO2 / CaO molar ratio of 0.9, and added into a reactor for hydrothermal synthesis reaction; the reaction temperature is controlled at 230-240°C, the stirring speed is 50-80rpm, and the reaction time is 1.5-2h.
[0011] The generated wollastonite calcium silicate hydrate crystals are fibrous. From their structural formula, it can be seen that the ideal wollastonite calcium silicate hydrate crystals have no structural water, let alone free water. Only two hydroxyl groups are connected to Ca to form a distorted octahedron [CaO4(OH)2], which is the phase with the lowest water content among all calcium silicate hydrates. The wollastonite calcium silicate hydrate has good thermal stability.
[0012] ④ Add the synthesis accelerator Na2SiO3 to the mixed solution of step ③ at a Na2SiO3 / CaO molar ratio of 0.1, so that the final SiO2 / CaO molar ratio of the mixed solution reaches 1:1; maintain the reaction temperature at 230-240°C, continue the reaction for 1.0h, and stir at a rate of 30-50rpm. The mass concentration of the synthesis accelerator Na2SiO3 is 0.3kg / L, and the modulus is 3.5-3.6.
[0013] Na in synthetic accelerator+ Increased crystallinity of wollastonite calcium silicate hydrate crystals, Na + The entry of Na reduces the interplanar spacing of the lattice in the direction of the crystal axis, and the microscopic morphology develops towards elongation. + The occupation of the crystal affects the Si-O bond length of the nearby silicon-oxygen tetrahedron and the stretching factor of the silicon double chain. In order to offset the structural instability caused by the reduction of the stretching factor, the silicon double chain shrinks and adjusts, and can increase adhesion to form a physical bond.
[0014] The main reaction formula of the synthetic accelerator Na2SiO3 and Ca(OH)2 is:
[0015] mCa(OH)2+nSiO2(OH)2 -2 →mCaO·nSiO2·xH2O+2nOH - +(mx)H2O
[0016] Si 4+ Located in [SiO4] 4- The center of the tetrahedron constitutes the basic structural unit, Ca 2+ Ions interact with water and diffuse into the crystal lattice to form calcium silicate hydrate crystals through ion exchange, intracrystalline diffusion or hydration crystallization.
[0017] ⑤ According to step ①, 25-30% of the mass of the tailings powder is taken as a nucleation enhancer; 2% of the mass of the wollastonite mineral fiber is added with 0.2 mol / L dilute hydrochloric acid to activate its surface; the particle size of the wollastonite mineral fiber is 74um, and the aspect ratio is 15-20:1.
[0018] The use of dilute hydrochloric acid with a relatively low concentration aims to produce an activation effect only on the surface of the mineral fiber, while the internal structure of the mineral fiber remains unchanged, and its mechanical properties such as compressive strength and flexural strength are not affected by the activation, thereby achieving the technical effect of enhancing the internal structural force of the product and making the product produce high strength.
[0019] ⑥ Add the wollastonite mineral fiber activated in step ⑤ to the reactant obtained in step ④ and mix with other raw materials; the stirring rate is 100-120 rpm, and the mixing time is 0.8-1.0 h.
[0020] The activated wollastonite mineral fiber acts as a nucleating agent, which can produce a dense matrix on its surface and graft crystallize to form a calcium silicate hydrate grid; its inherent fiber reinforcement effect and the newly generated fiber crystal coating will further enhance the strength of the synthetic wollastonite refined slag product.
[0021] ⑦ The material obtained in step ⑥ is pressed and molded to obtain a spheroid of Φ15-20 mm, wherein the molding pressure is 30-40 MPa; the molded spheroid is cured for 10 hours at a temperature of 180-200° C. and 0.8 MPa saturated steam.
[0022] As the curing time increases, calcium silicate hydrate will form a xonotlite structure, and the relative strength and crystallinity will increase significantly. By 10 hours, a xonotlite with a high degree of crystallinity has been formed.
[0023] ⑧ A two-stage gasifier is used to supply gas to the vertical furnace to perform low-temperature calcination on the spheroids after curing in step ⑦; the upper stage gas of the gasifier is connected to the preheating nozzle of the vertical furnace after passing through a purification system, and the outlet temperature of the upper stage gas is controlled at 100-120° C.; the lower stage gas of the gasifier is connected to the calcining nozzle of the vertical furnace after passing through a purification system, and the outlet temperature of the lower stage gas is controlled at 450-550° C.; the ratio of the upper stage gas flow to the lower stage gas flow is 1:4-5; the vertical furnace is provided with a heat storage wind box, and the heat storage wind box preheats the air and supplies oxygen to the preheating nozzle and the calcining nozzle respectively.
[0024] A double-stage gasifier is used. According to the relevant properties of the coal entering the furnace, the supply of gas generated by the gasification stage is adjusted during operation, that is, the ratio of the upper and lower gas of the generator is effectively adjusted, and the coal entering the furnace is thoroughly dried and distilled, so as to improve the calorific value of the gas under the premise of ensuring the normal and stable operation of the generator system. The upper stage gas is a distillation gas mainly composed of alkane gas. Because of its low temperature, it is suitable for the preheating exhaust of spheroids, and can avoid the occurrence of spheroid explosion caused by excessive temperature. The lower stage gas is a gas with CO and H2 as the main components. Because of its high temperature, it is suitable for the sintering of spheroids. According to the different temperature requirements of the upper and lower stages of gas, the requirements of the system equipment for gas technical indicators are met by controlling the ratio of gas flow. The purification system adopts different purification methods according to the different characteristics of the upper stage gas and the lower stage gas to obtain the best effect.
[0025] As a heating source, electricity is a relatively good heating source, except that energy consumption accounts for a large proportion of the cost. It is suitable for use in small-scale production and very high product profits. The environmental problems caused by direct combustion of coal require a certain amount of investment to solve the emission of dust and flue gas pollution, and the problem of temperature control accuracy is not suitable for larger-scale production processes. Natural gas, as a relatively efficient and clean energy, requires a large amount of infrastructure equipment and safety investment to build a new gas station in the absence of a natural gas pipeline supply; therefore, using coal gas as a heating source in the production process of synthetic wollastonite refined slag is a relatively suitable choice.
[0026] ⑨ The length of the preheating section of the vertical furnace is more than 1 / 3 of the length of the furnace body, the preheating nozzle is arranged at the lower edge of the preheating section, the temperature of the preheating section is controlled to be 200-260°C, and the preheating time is 20-25min; the calcining nozzle is arranged at the lower edge of the calcining section, the temperature of the calcining section is controlled to be 780-830°C, and the calcining time is 20-25min; the synthetic wollastonite refined slag after calcination is cooled in the cooling section and discharged from the finished product outlet.
[0027] The furnace body of the vertical furnace is provided with a preheating section, a calcining section and a cooling section in order from top to bottom. The length of the preheating section is preferably 2 / 5-3 / 5 of the length of the furnace body. By lengthening the length of the preheating section, the moisture in the spheroid can be slowly discharged without destroying the internal structure, so that the structural strength is maintained. The length of the calcining section is equal to 1 / 3 of the length of the furnace body, and the length of the cooling section is less than 1 / 3 of the length of the furnace body. Because the firing temperature is low, the distance of the cooling section can be shortened to further save heat energy and improve production efficiency.
[0028] A synthetic wollastonite refined slag prepared according to the preparation method and its application in a molten steel purification process. Since the synthetic wollastonite refined slag product has high purity and high particle strength, it is preferably applied to the purification of molten steel of cord steel.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] ① Aiming at the problems of high energy consumption, high pollution and high emission in producing molten wollastonite refined slag, the present invention adopts a low-temperature sintering method to reduce the energy consumption of the product; the temperature is reduced from the firing temperature of 1600°C in the melting method to about 800°C, saving more than 50% of energy consumption; it has multiple effects such as energy saving, carbon reduction and environmental protection.
[0031] ② The particle diameter and particle strength of the synthetic wollastonite refined slag product are improved, solving the disadvantages of small pre-melted refined slag particles and high dust generation in the steelmaking process in the prior art. At the same time, it also overcomes the related technical problems of sintering products directly formed in the rotary kiln. Although the firing temperature of such products is as high as 1350-1550℃, their product strength is still very low, and they are easy to break and pulverize during packaging, transportation, and use, thus generating dust during use, polluting the environment, and wasting raw materials.
[0032] ③ The preparation of refined slag with wollastonite tailings realizes high-quality graded utilization of resources, breaks through the technical bottleneck of "tailings-free development and application", highlights the advanced nature of the technology, and conforms to the concept of sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is the XRD spectrum of synthetic wollastonite refining slag;
[0034] Figure 2This is a schematic diagram of the process structure for preparing synthetic wollastonite refined slag;
[0035] In the figure: 1-two-stage gasifier; 2-vertical furnace; 11-coal adding mechanism; 12-upper gas outlet; 13-upper gas purification system; 14-lower gas purification system; 15-lower gas outlet; 16-steam (air) inlet; 21-preheating nozzle; 22-feeding port; 23-smoke outlet; 24-calcining nozzle; 25-heat storage wind box; 26-cooling air inlet; 27-finished product outlet. DETAILED DESCRIPTION
[0036] The present invention is further described below in conjunction with specific embodiments, but the present invention is not limited in any way. To avoid repetition, the raw materials in the following embodiments are all commercially available products unless otherwise specified, and the methods used are all conventional methods unless otherwise specified. The chemical composition of raw materials and finished products is detected according to GB / T14506.3-2010 "Chemical Analysis Methods for Silicate Rocks"; the particle strength of the product is determined according to the standard GB / T14201-2018 "Determination of the Compressive Strength of Iron Pellets for Blast Furnaces and Direct Reduction"; an X-ray diffractometer (Cu target) is used to identify the type of phase of the prepared product, and the working parameters of the XRD test are: tube voltage 40kV, tube current 40mA, λ is 0.15406nm, scanning range 3~70°, etc.
[0037] The preparation process of synthetic wollastonite refined slag is as follows: Figure 2As shown, the process equipment includes a two-stage coal gasifier 1 and a vertical furnace 2. The top of the two-stage coal gasifier 1 is provided with a coal feeding mechanism 11. Qualified raw coal is transported and lifted to the coal storage bin by a belt conveyor, and then added to the furnace in batches through the coal feeding mechanism 11. The coal undergoes dry distillation. After dry distillation, the semi-coke state of the coal reacts with the gasification agent (air, steam) input from the steam inlet 16. The coal gas generated above is divided into two parts: upper coal gas and lower coal gas. The upper coal gas passes through the upper coal gas purification system 13 from the upper coal gas outlet 12 and is connected to the preheating nozzle 21 of the vertical furnace. The lower coal gas passes through the lower coal gas purification system 14 from the lower coal gas outlet 15 and is connected to the calcining nozzle 24 of the vertical furnace; the preheating nozzle 21 and the calcining nozzle 24 of the vertical furnace are both paired and evenly and symmetrically arranged on the furnace body. The heat storage wind box 25 of the vertical furnace preheats the air and supplies oxygen to the preheating nozzle 21 and the calcining nozzle 24 respectively, thereby improving the thermal energy utilization efficiency. After the coal gas completes the combustion reaction, the generated waste gas is discharged from the flue gas outlet 23, and is treated for environmental protection and discharged after meeting the standards. The cured spheroids are added from the feed port 22 of the vertical furnace. The temperature of the preheating section is controlled at 200-260°C by adjusting the gas flow rate of several preheating nozzles 21 and the ratio of preheating oxygen; the temperature of the calcining section is controlled at 780-830°C by adjusting the gas flow rate of several calcining nozzles 24 and the ratio of preheating oxygen, and the calcining time is controlled at 20-25min. After calcination, the spheroids stay in the cooling section for a period of time to complete their chemical reaction, recrystallization, and recrystallization, and then are discharged from the finished product outlet 27.
[0038] Example 1
[0039] A method for preparing synthetic wollastonite refined slag, the method comprising the following steps:
[0040] Take wollastonite tailings with SiO2 content of 76.3% and CaO content of 20.8%, grind them into tailings powder with a pass rate of 98% at 800 mesh, add water to adjust the tailings powder into a slurry with a mass concentration of 40%. Take lime with a CaO content of 88%, add water according to 40% of CaO mass to digest it into lime milk, the digestion temperature is 95℃, the digestion time is 40min, and the stirring speed is 500rpm. The above tailings powder slurry and lime milk are prepared according to the SiO2 / CaO molar ratio of 0.9, and added to the reactor for hydrothermal synthesis reaction; control the reaction temperature to 240℃, the stirring speed to 80rpm, and the reaction time to 2h. To the above-mentioned mixed solution, add a synthetic accelerator Na2SiO3 with a mass concentration of 0.3kg / L and a modulus of 3.5 according to a Na2SiO3 / CaO molar ratio of 0.1, so that the final SiO2 / CaO molar ratio of the mixed solution reaches 1:1; maintain the reaction temperature at 240°C, continue the reaction for 1.0h, and stir at a rate of 50rpm. Take 30% of the mass of the tailings powder with a particle size of 74um and an aspect ratio of 20:1 as a nucleation enhancer, and add 2% of the mass of the wollastonite mineral fiber with a concentration of 0.2mol / L dilute hydrochloric acid for surface activation. Add the above-mentioned activated wollastonite fiber to the reactant and mix with other raw materials; stir at a rate of 120rpm and mix for 1.0h. Press the above-mentioned material to obtain a Φ20mm spheroid, and the molding pressure is 40Mpa; the molded spheroid is cured for 10h at a temperature of 200°C and 0.8MPa saturated steam.
[0041] A two-stage gasifier is used to supply gas to a vertical furnace to calcine the spheroids; the upper stage gas of the gasifier is connected to the preheating nozzle of the vertical furnace after passing through a purification system, and the outlet temperature of the upper stage gas is controlled at 120°C; the lower stage gas of the gasifier is connected to the calcining nozzle of the vertical furnace after passing through a purification system, and the outlet temperature of the lower stage gas is controlled at 550°C; the ratio of the upper stage gas flow rate to the lower stage gas flow rate is 1:4; the heat storage wind box of the vertical furnace preheats the air and supplies oxygen to the preheating nozzle and the calcining nozzle; the length of the preheating section of the vertical furnace is 3 / 5 of the length of the furnace body, and the length of the calcining section is equal to 1 / 3 of the length of the furnace body, the preheating nozzle is arranged at the lower edge of the preheating section, the temperature of the preheating section is controlled to be 260°C, and the preheating time is 25 minutes; the calcining nozzle is arranged at the lower edge of the calcining section, the temperature of the calcining section is controlled to be 830°C, and the roasting time is 25 minutes; the calcined synthetic wollastonite refined slag is cooled and discharged from the finished product outlet. The performance test results of the prepared products are shown in Table 1.
[0042] The product of Example 1 was analyzed by XRD, and the spectrum is as shown in the attached Figure 1The crystal structure of wollastonite is shown, which proves that the reaction is complete. The diameter of the product particles is 20mm, and the particle size is uniform; the particle strength reaches 5400N, with high strength and not easy to break. From the results of chemical composition analysis, the basicity is neutral, which is conducive to molten steel refining; in particular, the Al2O3 content is very small, only 0.20wt%, which can meet the unique requirements of special steel for refining slag.
[0043] Example 2
[0044] A method for preparing synthetic wollastonite refined slag, the method comprising the following steps:
[0045] Take wollastonite tailings with SiO2 content of 75.2% and CaO content of 18.6%, grind them into tailings powder with a pass rate of 97% at 800 mesh, add water to adjust the tailings powder into a slurry with a mass concentration of 40%. Take lime with a CaO content of 86.3%, add water according to 40% of CaO mass to digest it into lime milk, the digestion temperature is 95℃, the digestion time is 30min, and the stirring speed is 450rpm. The above tailings powder slurry and lime milk are prepared according to the SiO2 / CaO molar ratio of 0.9, and added to the reactor for hydrothermal synthesis reaction; control the reaction temperature to 235℃, the stirring speed to 70rpm, and the reaction time to 1.8h. To the above-mentioned mixed solution, add a synthetic accelerator Na2SiO3 with a mass concentration of 0.3kg / L and a modulus of 3.6 according to a Na2SiO3 / CaO molar ratio of 0.1, so that the final SiO2 / CaO molar ratio of the mixed solution reaches 1:1; maintain the reaction temperature at 235°C, continue the reaction for 1.0h, and the stirring rate is 40rpm. According to 28% of the mass of the tailings powder, wollastonite mineral fiber with a particle size of 74um and an aspect ratio of 18:1 is taken as a nucleation enhancer, and 2% of the mass of the wollastonite mineral fiber is added with a concentration of 0.2mol / L dilute hydrochloric acid for surface activation. The activated wollastonite fiber is added to the reactant and mixed with other raw materials; the stirring rate is 110rpm and mixed for 0.9h. The above-mentioned material is pressed and molded to obtain a Φ18mm spheroid, and the molding pressure is 35Mpa; the molded spheroid is cured for 10h at a temperature of 190°C and 0.8MPa saturated steam.
[0046] A two-stage gasifier is used to supply gas to a vertical furnace to calcine the spheroids; the upper stage gas of the gasifier is connected to the preheating nozzle of the vertical furnace after passing through a purification system, and the outlet temperature of the upper stage gas is controlled at 100°C; the lower stage gas of the gasifier is connected to the calcining nozzle of the vertical furnace after passing through a purification system, and the outlet temperature of the lower stage gas is controlled at 450°C; the ratio of the upper stage gas flow rate to the lower stage gas flow rate is 1:5; the heat storage wind box of the vertical furnace preheats the air and supplies oxygen to the preheating nozzle and the calcining nozzle; the length of the preheating section of the vertical furnace is 2 / 5 of the length of the furnace body, and the length of the calcining section is equal to 1 / 3 of the length of the furnace body, the preheating nozzle is arranged at the lower edge of the preheating section, the temperature of the preheating section is controlled to be 200°C, and the preheating time is 20 minutes; the calcining nozzle is arranged at the lower edge of the calcining section, the temperature of the calcining section is controlled to be 780°C, and the roasting time is 20 minutes; the calcined synthetic wollastonite refined slag is cooled and discharged from the finished product outlet. The performance test results of the prepared products are shown in Table 1.
[0047] The diameter of the synthetic wollastonite refined slag product of Example 2 is 18 mm, and the particle size is uniform; the particle strength reaches 5400N, the strength is high, and it is not easy to break. From the results of chemical composition analysis, the basicity is neutral, which is conducive to molten steel refining; in particular, the Al2O3 content is very small, only 0.15wt%, which can meet the unique requirements of special steel for refined slag.
[0048] Example 3
[0049] A method for preparing synthetic wollastonite refined slag, the method comprising the following steps:
[0050] Take wollastonite tailings with SiO2 content of 73.4% and CaO content of 19.7%, grind them into tailings powder with a pass rate of 98% at 800 mesh, add water to adjust the tailings powder into a slurry with a mass concentration of 40%. Take lime with a CaO content of 85.8%, add water according to 40% of CaO mass to digest it into lime milk, the digestion temperature is 95℃, the digestion time is 35min, and the stirring speed is 480rpm. The above tailings powder slurry and lime milk are prepared according to the SiO2 / CaO molar ratio of 0.9, and added to the reactor for hydrothermal synthesis reaction; control the reaction temperature to 230℃, the stirring speed to 50rpm, and the reaction time to 1.5h. To the above-mentioned mixed solution, add a synthetic accelerator Na2SiO3 with a mass concentration of 0.3kg / L and a modulus of 3.5 according to a Na2SiO3 / CaO molar ratio of 0.1, so that the final SiO2 / CaO molar ratio of the mixed solution reaches 1:1; maintain the reaction temperature at 230°C, continue the reaction for 1.0h, and the stirring rate is 30rpm. According to 25% of the mass of the tailings powder, wollastonite mineral fiber with a particle size of 74um and an aspect ratio of 15:1 is taken as a nucleation enhancer, and 2% of the mass of the wollastonite mineral fiber is added with a concentration of 0.2mol / L dilute hydrochloric acid for surface activation. The activated wollastonite fiber is added to the reactant and mixed with other raw materials; the stirring rate is 100rpm and mixed for 0.8h. The above-mentioned material is pressed and molded to obtain a Φ15mm spheroid, and the molding pressure is 30Mpa; the molded spheroid is cured for 10h at a temperature of 180°C and 0.8MPa saturated steam.
[0051] A two-stage gasifier is used to supply gas to a vertical furnace to calcine the spheroids; the upper stage gas of the gasifier is connected to the preheating nozzle of the vertical furnace after passing through a purification system, and the outlet temperature of the upper stage gas is controlled at 110°C; the lower stage gas of the gasifier is connected to the calcining nozzle of the vertical furnace after passing through a purification system, and the outlet temperature of the lower stage gas is controlled at 500°C; the ratio of the upper stage gas flow rate to the lower stage gas flow rate is 1:4; the heat storage wind box of the vertical furnace preheats the air and supplies oxygen to the preheating nozzle and the calcining nozzle; the length of the preheating section of the vertical furnace is 3 / 5 of the length of the furnace body, and the length of the calcining section is equal to 1 / 3 of the length of the furnace body, the preheating nozzle is arranged at the lower edge of the preheating section, the temperature of the preheating section is controlled to be 230°C, and the preheating time is 25 minutes; the calcining nozzle is arranged at the lower edge of the calcining section, the temperature of the calcining section is controlled to be 800°C, and the roasting time is 25 minutes; the calcined synthetic wollastonite refined slag is discharged from the finished product outlet after cooling. The performance test results of the prepared products are shown in Table 1.
[0052] The diameter of the synthetic wollastonite refined slag product of Example 3 is 15 mm, and the particle size is uniform; the particle strength reaches 5400N, the strength is high, and it is not easy to break. From the results of chemical composition analysis, the basicity is neutral, which is conducive to molten steel refining; in particular, the Al2O3 content is very small, only 0.11wt%, which can meet the unique requirements of special steel for refined slag.
[0053] Comparative Example 1
[0054] The fusion method is used to prepare wollastonite refined slag, the method comprising the following steps:
[0055] Oxides and calcium fluoride containing elements such as calcium, silicon, aluminum, magnesium, sodium, boron, and barium are made by crushing and mixing natural wollastonite, silica, calcite, feldspar, fluorite and other raw materials, and then putting them into a kiln, heating them with gas, sintering them at 1600℃ into a molten liquid state, and then cooling them by water quenching. The physical and chemical properties of the finished product are tested, as shown in Table 1. The content of impurities such as MgO and Al2O3 in its chemical composition is significantly increased, which limits its application. For example, it cannot be used in the refining process of cord steel with strict requirements on alumina content. At the same time, the particle diameter of the product is small, only 1-2mm, which is easy to generate dust, pollute the environment, and waste raw materials.
[0056] Comparative Example 2
[0057] The sintering method is used to prepare wollastonite refined slag, and the method comprises the following steps:
[0058] Grind natural wollastonite, quartz, limestone or calcite, fluorite, bauxite and other raw materials into powder, mix the powder raw materials evenly and directly put them into the rotary kiln, calcine them at 1350-1550℃ until they are agglomerated and then transferred out of the kiln to obtain sintered calcium silicate refined slag. The physical and chemical properties test results of the finished product are shown in Table 1. The content of impurities such as MgO and Al2O3 in its chemical composition is significantly increased, which limits its application. For example, it cannot be used in the cord steel refining process with strict requirements on alumina content. At the same time, the particle strength of the product is low, only 375N, and it is easy to break and generate dust, which affects the use effect.
[0059] Table 1 Performance test results of each refined slag product in the embodiments and comparative examples
[0060]
[0061] Application Example 1
[0062] The synthetic wollastonite refined slag product prepared in Example 1 was used in a steel plant to carry out cord steel refining practice. The scanning electron microscope analysis of the longitudinal section of the cord steel wire produced by the process showed that after the product was used for molten steel purification and refining, the inclusions of type A sulfide and type C silicate in the wire were significantly reduced, eliminating the influence of these two types of inclusions on the drawing performance; both type B and type D inclusions were level 0.5, and the number of type B was very small, the size of the inclusions was also significantly reduced, and semi-plastic and plastic inclusions were the main ones, and the cleanliness of the molten steel was greatly improved; the control of the elements of the finished product was basically stable, and the composition fluctuation between each heat was very small. The sulfur element was controlled below 0.003%, reaching a higher standard, the phosphorus element was controlled below 0.015%, the aluminum element was controlled below 0.0012%, and the titanium element was also controlled below 0.0008%. The control of each harmful element was stable and up to standard, thereby improving the technical level of clean steel.
[0063] For any technician familiar with the art, without departing from the scope of the technical solution of the present invention, the technical content disclosed above can be used to make many possible changes and modifications to the technical solution of the present invention, or modified into equivalent embodiments with equivalent changes. Therefore, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention should still fall within the scope of protection of the technical solution of the present invention.
Claims
1. A method for preparing synthetic wollastonite refined slag, characterized in that: The method comprises the following steps: ① Grind wollastonite tailings with a SiO2 mass content greater than 70% and a CaO mass content greater than 18% into tailings powder with a pass rate of greater than 95% at 800 mesh, and add water to prepare the tailings powder into a slurry with a mass concentration of 40%; ② Take lime with a CaO content greater than 85%, add water at 40% of the CaO content to dissolve it into lime milk, the dissolution temperature is 95°C, the dissolution time is 30-40 min, and the stirring speed is 450-500 rpm; ③ The tailings powder slurry obtained in step ① and the lime milk obtained in step ② are mixed at a SiO2 / CaO molar ratio of 0.9, and added into a reactor for hydrothermal synthesis reaction; the reaction temperature is controlled at 230°C-240°C, the stirring speed is 50-80 rpm, and the reaction time is 1.5-2 h; ④ Add the synthesis promoter Na2SiO3 to the mixed solution of step ③ at a Na2SiO3 / CaO molar ratio of 0.1, so that the final SiO2 / CaO molar ratio of the mixed solution reaches 1:1; maintain the reaction temperature at 230°C-240°C, continue the reaction for 1.0 h, and control the stirring rate to 30-50 rpm; ⑤ According to 25%-30% of the mass of the tailings powder in step ①, wollastonite mineral fiber is taken as a nucleation enhancer; 2% of the mass of the wollastonite mineral fiber is added with 0.2 mol / L dilute hydrochloric acid to activate its surface; ⑥ Add the activated wollastonite mineral fiber in step ⑤ to the reactant obtained in step ④ and mix with other raw materials; the stirring rate is 100-120 rpm, and the mixing time is 0.8-1.0 h; ⑦ Pressing and molding the material obtained in step ⑥ to obtain spheroids with a diameter of 15-20 mm, wherein the molding pressure is 30-40 MPa; curing the molded spheroids at a temperature of 180° C. to 200° C. and 0.8 MPa saturated steam for 10 h; ⑧ A two-stage gasifier is used to supply gas to the vertical furnace to perform low-temperature calcination on the spheroids after curing in step ⑦; the upper stage gas of the gasifier is connected to the preheating nozzle of the vertical furnace after passing through a purification system, and the outlet temperature of the upper stage gas is controlled at 100°C-120°C; the lower stage gas of the gasifier is connected to the calcining nozzle of the vertical furnace after passing through a purification system, and the outlet temperature of the lower stage gas is controlled at 450°C-550°C; the ratio of the upper stage gas flow rate to the lower stage gas flow rate is 1:4-5; the vertical furnace is provided with a heat storage wind box, and the heat storage wind box preheats the air and supplies oxygen to the preheating nozzle and the calcining nozzle respectively; ⑨ The length of the preheating section of the vertical furnace is more than 1 / 3 of the length of the furnace body, the preheating nozzle is arranged at the lower edge of the preheating section, the temperature of the preheating section is controlled at 200℃-260℃, and the preheating time is 20-25 min; the temperature of the calcining section is controlled at 780℃-830℃, and the calcining time is 20-25 min; the synthetic wollastonite refined slag after calcination is cooled in the cooling section and discharged from the finished product outlet.
2. The preparation method according to claim 1, characterized in that In step ④, the mass concentration of the synthesis accelerator Na2SiO3 is 0.3 kg / L, and the modulus M is 3.5-3.6; in step ⑤, the particle size of the wollastonite mineral fiber is 74 μm, and the aspect ratio is 15-20:
1.
3. The preparation method according to claim 1, characterized in that: The purification system in step ⑧ adopts different purification methods according to the different characteristics of the upper gas and the lower gas.
4. The preparation method according to claim 1, characterized in that: The length of the calcination section in step ⑨ is equal to 1 / 3 of the length of the furnace body.
5. Use of the synthetic wollastonite refined slag prepared according to any one of claims 1 to 4 in a molten steel purification process.
